Kant on euthanasia and the duty to die: clearing the air. Issue 8 (22nd September 2014) - Cholbi, Michael
Abstract : Thanks to recent scholarship, Kant is no longer seen as the dogmatic opponent of suicide that he appears to be at first glance. However, some interpreters have recently argued for a Kantian view of the morality of suicide with surprising, even radical, implications. More specifically, they have argued that Kantianism (1) requires that those with dementia or other rationality-eroding conditions end their lives before their condition results in their loss of identity as moral agents and (2) requires subjecting the fully demented or those confronting future dementia to non-voluntary euthanasia. Properly understood, Kant's ethics have neither of these implications (1) wrongly assumes that rational agents' duty of self-preservation entails a duty of self-destruction when they become non-rational, (2) further neglects Kant's distinction between duties to self and duties to others and wrongly assumes that duties can be owed to rational agents only during the time of their existence.